Diagnosis of Interstitial Fibrosis and Tubular Atrophy in Kidney Allograft: Implementation of MicroRNAs (Iranian Journal of Kidney Diseases, 2014)
Chronic allograft nephropathy is the major cause of kidney allograft loss, and recent advances in immunosuppression therapy do not alter the picture. Interstitial fibrosis and tubular atrophy is an early event that starts early after engraftment and even could be found in recipients with good allograft function. Serum creatinine and estimated glomerular filtration rate have limited clinical roles in estimating the histopathological changes and graft fibrosis. Recent progress in microRNA research has created a great promise to identify new diagnostic biomarkers and therapeutic targets in renal fibrosis.